THE UNCONTROLLED VOTE. MUNICIPAL ELECTIONS AND CIVIL WAR IN PERU (1856-1858) (Tzintzun, Revista de Estudios Históricos, 2024)
This paper analyzes the holding of municipal elections in Peru in the context ofthe civil war that pitted the provisional liberal government of General RamónCastilla against the conservative rebel army of General Manuel Ignacio deVivanco between November 1856 and March 1858. I argue that these electionswere not directly affected by the war, but were occasionally conditioned by a“civil war” discourse. This rhetoric when activated came to question thefunctioning of municipalities, as was the case of the municipality of the city ofLima accused of conspiracy.
Keywords: municipalities; elections; civil war; Pertu; XIX century